Vegetable dietary fibres made with minimal processing improve health-related faecal parameters in a valid rat model. Issue 6 (24th May 2016) - Monro, John; Mishra, Suman; Redman, Claire; Somerfield, Sheryl; Ng, Jovyn
Abstract : Structural components in tissues of minimally processed vegetables substantially increase faecal bulk and hydration capacity much more than fermentable fibres. Abstract : Dietary fibre-induced faecal bulking and hydration are important contributors to large bowel function and health, and are affected by the dietary fibre structure. To determine faecal bulk-related parameters for vegetable dietary fibres with retained structure, cold water fragmentation of vegetables was used to make minimally processed vegetable fibres (MPVF) from swede, broccoli and asparagus. A valid adult rat model was used to subject the fibres to processes of hind gut fermentation and faecal accumulation similar to those in humans. All the MPVFs had high faecal bulking indexes (FBIs, mean ± sem: wheat bran (reference), 100 ± 6.0; asparagus 168 ± 5.7; swede 135 ± 6.1; broccoli 135 ± 5.9; broccoli rind 205 ± 10.4), and caused large increases in the theoretical colonic water load at 10 g per 100 g diet (increase over baseline (%): wheat bran, 137 ± 8.3; asparagus, 236 ± 25, swede 193 ± 8.8; broccoli 228 ± 12; broccoli rind 223 ± 8.5). Faecal bulking by MPVFs was much greater than by fermentable extracted polysaccharides such as pectin and raftilose, or by commercial fibres made from highly processed cell walls. The results show natural, non-degraded vegetable fibres with retained botanical structure have beneficial effects not provided by structure-less fermentable dietary fibres. Dietary fibre-deficient diets supplemented with prebiotics cannot, therefore, adequately substitute for varied diets containing adequate vegetables, fruits and wholegrain cereals in which fermentation is associated with enough retained structure to conserve physicochemical properties of benefit to colonic function.